A Morphological Study of Poly (Vinylidene Fluoride) Pvdf Membranes: In Perspective of Membrane Pervaporation Process - Adil Hatem Rashid; M. D. Irfan Hatem; Muhammad Syarhabil Ahmad; Mohd. Hafiz Dzarfan Othman (ASEAN Journal of Chemical Engineering, 2015)
Membrane separation plays an important role in chemical industry (Prabhat et al. 2011). Pervaporation is one of the most promising membrane separation processes which is used in a wide range of applications such as separation of organic mixtures and dehydration of solvents. This study investigated the effect of polymer concentration on the morphology of pervaporation membrane, where polyvinylidene fluoride (PVDF) was chosen as the base polymeric material while phase inversion method was employed as a technique to prepare an asymmetric PVDF membrane. The polymer concentration in dope solution was varied from 16 to 20wt% and the prepared membranes were characterized in terms of its structure, porosity, contact angle, and pore size. Five PVDF membrane samples were prepared (without any post-treatment) with polymer concentration of 16, 17, 18, 19, and 20wt% respectively. Depending on permeating component, two main areas of pervaporation processes can be identified: hydrophobic and hydrophilic and consequently two types of membranes could be observed: hydrophobic and hydrophilic membranes. From the results, it was found that the increase in polymer concentration has produced membranes with low pore size and porosity and as a result, high contact angle (low hydrophilicity).The highest contact angle of 83º was found for membrane with highest polymer concentration of 20wt% with the lowest pore size and porosity of (0.4156µm and 65%) respectively. The lowest contact angle of 76º was found for membrane with the lowest polymer concentration of 16wt% with the highest pore size and porosity (0.8671µm and78%) respectively.